A guide for the meaningful surface analysis of wood by XPS and ToF‐SIMS. (11th January 2022) - Watts, John F.; Goacher, Robyn E.
Abstract : The surface analysis of wood and wood products is becoming increasingly important for reasons ranging from the investigation of molecular constituents through to the optimization of industrial processes. As with any natural product, wood analysis is not straightforward, and this review aims to provide guidance for the successful surface analysis of wood by XPS and ToF‐SIMS. Through example experiments, three themes are addressed relevant to obtaining meaningful results: considerations related to heterogeneity in the composition of wood (e.g., growth rings); the impact of the chemical removal of minor wood components known as extractives, and whether such a process is necessary; and the potential for misleading or erroneous results as a result of contamination occurring during sample preparation. In addition to discussing successful sample preparation approaches, the important role to be played by MVA in surface analysis is emphasized, particularly in the analysis of ToF‐SIMS data. Examples of ToF‐SIMS/MVA are provided that highlight the identification of contamination in sample preparation, the quantification of wood composition in terms of cellulose and lignin, and the indication of age of softwood samples. Through consideration of the complexities that influence wood surface analysis, the design and interpretation of consequential experiments become easier and more accurate.